Anti-ulcer effect of azadirachta indica (neem) and eupatorium triplinerve (ayyappana) in rats - Sangeetha Satheesan (Department of Pharmacology and Toxicology, College of Veterinary and Animal Sciences, 2005)
The present study was conducted in adult albino rats to assess the anti-ulcer effect of alcoholic extract and powder of leaves of Azadirachta indica and Eupatorium triplinerve in comparison with famotidine, a standard anti-ulcer drug. Ninety six rats weighing 150-200gm body weight of either sex divided into twelve groups were used for the study with eight rats in each group. Group 1 was administered the vehicle, five per cent gum acacia for seven days where as group 2 was administered aspirin at the dose of 200mg/kg for seven days. Group 3 was administered aspirin for seven days and from 8th day onwards, they were maintained by normal feeding and watering for 20 days to assess the natural healing. Famotidine, a standard anti-ulcer drug was given at the dose of 40mg/kg for 20 days following aspirin administration to the group 4 animals. The alcoholic extract and powder of A.indica and E.triplinerve were administered to the treatment groups (Groups 5-12) at the two dose levels of 250mg/kg, 500mg/kg and 500mg/kg, 1000mg/kg respectively for 20 days following aspirin administration. The control group as well as the aspirin group were sacrificed on the 8th day, whereas all the other groups were sacrificed on 28th day. The number of ulcers and severity (ulcer score) were determined with the help of magnifying lens and the ulcer index and healing index were calculated. Various biochemical parameters were studied to confirm the anti-ulcer activity of the plant preparations under study. The degree of lipid peroxidation, as well as the anti-oxidant enzyme status, namely, superoxide dismutase and catalase levels were assessed in gastric mucosa. The serum alkaline phosphatase activity was estimated on 28th day of the experiment. Body weight was taken at weekly intervals. Heamatological parameters such as total leucocyte count, differential count and haemoglobin count were determined to assess any changes in the haemogram. Histopathological study was also conducted to evaluate the severity of ulceration and healing process.